(untitled) (Research, Society and Development, 2019)
This article consists of a case study, where the objective was to perform a diagnosis of the system supply system and water treatment in the urban area of São Gonçalo do Rio Abaixo in Minas Gerais, exposing briefly the problems it currently presented , and consequently the predictability of actions with technical contributions, which can serve as aid to the municipal administration and civil society, in the elaboration of public policies and decision making, in the attempt to generate benefits for the entire population. Therefore, it was necessary to search for information in public documents, academic literature and current legislation to characterize the study area and collect data. And finally, presented a set of actions to be planned and you execute the immediate term, short, medium and long in order to promote the balance of the environment by means of a modifier and sustainable approach.